2008
DOI: 10.1302/0301-620x.90b6.19901
|View full text |Cite
|
Sign up to set email alerts
|

Schwannoma of the fibula

Abstract: We describe a schwannoma located in the mid-diaphyseal region of the fibula of a 14-year-old boy. Radiologically this was an expansile, lytic, globular and trabeculated lesion. MRI showed a narrow transition zone with a break in the cortex and adjacent tissue oedema. Differential diagnosis included schwannoma, fibrous dysplasia, giant cell tumour and aneurysmal bone cyst. The tumour was excised en bloc, with marginal resection limits, and there has been no recurrence two years after surgery. Histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Therefore, an intraosseous schwannoma involving a long bone may be associated with the second mechanism, the tumor arises and develops within the nutrient canal, and related to the site of the nutrient artery; however, the most common location of intraosseous schwannomas in long bones remains to be elucidated. A total of 4 cases of intraosseous schwannoma of the fibula were previously reported with clear radiographic figures (4)(5)(6), and 3 of these cases occurred in the diaphysis of the fibula. As free vascularized fibular grafts have been widely used to cover skeletal bone defects larger than 6 cm (16), it has been reported that the nutrient canal into the fibula is positioned between 12 and 18 cm from the tip of the fibula, in the diaphysis (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, an intraosseous schwannoma involving a long bone may be associated with the second mechanism, the tumor arises and develops within the nutrient canal, and related to the site of the nutrient artery; however, the most common location of intraosseous schwannomas in long bones remains to be elucidated. A total of 4 cases of intraosseous schwannoma of the fibula were previously reported with clear radiographic figures (4)(5)(6), and 3 of these cases occurred in the diaphysis of the fibula. As free vascularized fibular grafts have been widely used to cover skeletal bone defects larger than 6 cm (16), it has been reported that the nutrient canal into the fibula is positioned between 12 and 18 cm from the tip of the fibula, in the diaphysis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 200 cases have been previously reported; of these cases, the most common sites of the involved bones were the mandible and sacrum (2). Although a number of cases of intraosseous schwannoma involving the long bones have been previously reported (3)(4)(5)(6)(7)(8), this type of disease is relatively rare, and the typical location at which an intraosseous schwannoma of the long bones may arise is uncertain. Intraosseous schwannoma presents as a slowly enlarging and painless mass (8); however, if the bone becomes affected and a microfracture is caused, the mass becomes painful.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraosseous schwannomas (neurilemmomas) are rare benign neoplasms that account for \0.2% of primary bone tumors [5,11]. Except for the long bones, the most common site of involvement is the mandible, and only eight cases involving the mobile spine have been described in the English literature [1-4, 8-10, 12].…”
Section: Introductionmentioning
confidence: 99%